The ecology of calcareous fens in Park County, Colorado - Johnson, J. Bradley, author; Steingraeber, David A., advisor; Detling, James K., committee member; Dix, Ralph L., committee member; Scott, Michael L., committee member; MacDonald, Lee H., committee member (Colorado State University. Libraries, 2000)
Calcareous fens are wetlands which accumulate peat and have alkaline ground water as their dominant hydrologic input. This combination of environmental characteristics produces an unusual type of habitat and a large number of rare and regionally endemic plant and insect species are found within these fens. In spite of the ecological importance of calcareous fens, they have been subjected to a number of destructive land use practices, most commonly peat mining and drainage. The plant ecology and effects of disturbance in these wetlands were studied on three calcareous fens in South Park. The fens used in this study were chosen to represent the range and degrees of disturbance found within South Park wetlands. All the fens studied were classified as extremely rich, based on species indicators and water chemistry Detrended correspondence analysis, canonical correspondence analysis and two-way indicator species analysis (TWINSPAN) were used to evaluate fen vegetational patterns and classify vegetational assemblages. Vegetation on and between the fens reacts to five primary gradients: water table height, minerotrophy, microtopography, fen margin to expanse, and regional differences. Vegetation types resulting from these gradients were classified into five classes, eight subclasses, and twelve associations. An evaluation of the effects of peat mining and ditching were made in a comparative study of intact and disturbed portions of each fen. Peat mining was found to significantly impact vegetational composition, species richness and vegetative cover even many years after the cessation of the disturbance. Mining was also found to affect several soil attributes and water quality. Extremely high uranium levels were found to be closely associated with peat mining activity at one of the fens. Fen drainage was found to significantly change vegetational composition, soil structure, and several water chemistry parameters. Revegetation following experimental disruption was studied to elucidate patterns of secondary succession and evaluate the role of the soil propagule bank in fen restoration. Plots within experimental blocks were manipulated to approximate the effects of peat mining either with no restoration applied or with stockpiled peat reintroduced. Experimental manipulation had major effects on plot vegetation, although in blocks located in previously impacted areas plot vegetation rebounded quickly to near pre-treatment condition. In areas with intact wetland hydrology, seeds were found to play a minor role in revegetation with most growth originating from vegetative structures. In artificially drained areas, sexual reproduction was the dominant mode of revegetation. In essentially all cases, replacement of the upper 10cm of native soil significantly speeded revegetation by supplying the plot with native topsoil and viable sexual and asexual propagules. Based on these results, stockpiling and reintroduction of native topsoil is a recommended approach to restoring disturbed fens.
Keywords: ecology; botany